Synchronous Modes of Terrestrial and Marine Productivity in the North Pacific - Berkelhammer, Max (Frontiers in Earth Science, 2019)
The primary productivity of adjacent terrestrial and marine ecosystems can display synchronous responses to climate variability. Previous work has shown that this behavior emerges along the California coast where internal modes of climate variability, such as El Nino Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO), alter jet stream dynamics that influences marine ecosystems through upwelling and terrestrial ecosystems through precipitation. This study assesses whether marine-terrestrial synchrony is a widespread phenomenon across the North Pacific by utilizing satellite-derived Solar-Induced Fluorescence (SIF) and chlorophyll-a as proxies for land and sea productivity, respectively. The results show that terrestrial and marine ecosystems are consistently synchronized across 1000's of kms of the North Pacific coastline. This synchrony emerges because both marine and terrestrial ecosystems respond to climate modes with a similar north-south dipole pattern that is mirrored across the coastal interface. The synchrony is disrupted when PDO and ENSO oppose one another because the terrestrial north-south dipole follows the PDO while the marine pattern follows ENSO. The consequence is marine and terrestrial productivity anomalies that are opposite one another along adjacent regions of the coastline. If ENSO and the PDO have shared low-frequency variance, then synchrony would be the dominant state despite local topographic and trophic diversity along the coastlines. This result suggests that climate proxy stacks that include biotically sensitive marine and terrestrial proxies would have a selective sensitivity to modes such as PDO that drive synchrony. Lastly, the coupling of land and sea productivity may have the effect of generating amplified regional responses of the carbon budget to climate variability by simultaneously enhancing the terrestrial and marine carbon sinks.